An economic and sustainable approach to transform aluminosilicate-rich solid waste to functionally graded composite foam for high-temperature applications - Pandey V.; Kumar Yadav M.; Panda S.K.; Singh V.K. (My University, 2025)
The present study proposes an economical and effective approach for recycling coal overburden and similar solid wastes to fabricate lightweight and high-strength composite foam with industrial applications. Reaction-generated thermo-foaming technique has been used to develop functionally graded mullite-embedded silicate composite foam in a single step. The developed foams with gradient pores exhibit superior thermo-mechanical properties. In situ-growth of mullite phase within the silicate phase results in better mechanical strength of the foam. They possess bulk density, compressive strength and thermal conductivity in the range of 0.31–1.34 g/cm3, 2.97–15.06 MPa and 0.0843–0.2871 W/(m∙K), respectively. Thermal treatment irreversibly transforms the heavy metals present in the solid waste into stable mineral phases, further inhibiting the leaching of heavy metals from the developed foam. The developed foam with tuneable and gradient microstructure is seen as a potential material for thermal insulation and other applications such as refractories, molten metal and hot flue gas filters. © 2023 Elsevier Ltd